A 2D hydrodynamic model-based method for efficient flood inundation modelling. Issue 5 (29th July 2022) - Yang, Qi; Wu, Wenyan; Wang, Q. J.; Vaze, Jai
Abstract: Efficient and accurate flood inundation predictions can provide useful information for flood risk mitigation and water resource management. In this paper, we propose a new modelling method, LoHy +, which can be applied to efficiently simulate the spatiotemporal evolution of flood inundation with reasonable accuracy. The method integrates a low-fidelity two-dimensional (2D) hydrodynamic model and a mapping module to estimate water depth in a catchment during floods. The performance of the proposed modelling method was evaluated using a real-world catchment of approximate 2, 000 km 2, in the Southern Murray–Darling Basin, Australia. The results show that there is a good agreement between flood inundation obtained from the proposed method and that simulated using a high-fidelity 2D hydrodynamic model. The proposed method is much more efficient than the high-fidelity 2D hydrodynamic model, which makes it an alternative method for applications requiring many model runs or long simulation durations. Also, the LoHy+ model has the potential to be applied in flood inundation forecast, flood risk mitigation design water resource management, etc. HIGHLIGHTS: A new method, LoHy+, is developed to efficiently simulate flood inundation with reasonable accuracy. The existing hydrodynamic model is exploited to achieve higher computational efficiency. Relationships between flood water evolutions in the river and floodplain are revealed and applied to better achieve the computational efficiency while still guaranteeing the simulation accuracy with the use of LoHy + .